Modification of human β-globin locus PAC clones by homologous recombination in Escherichia coli - Imam, A. M. Ali (Oxford University Press, 2000)
We report here modifications of human β-globin PAC clones by homologous recombination in Escherichia coli DH10B, utilising a plasmid temperature sensitive for replication, the recA gene and a wild-type copy of the rpsL gene which allows for an efficient selection for plasmid loss in this host. High frequencies of recombination are observed even with very small lengths of homology and the method has general utility for introducing insertions, deletions and point mutations. No rearrangements were detected with the exception of one highly repetitive genomic sequence when either the E.coli RecA- or the lambdoid phage encoded RecT and RecE-dependent recombination systems were used.